2020
DOI: 10.1017/s1368980019004622
|View full text |Cite
|
Sign up to set email alerts
|

Body iron and lead status in early childhood and its effects on development and cognition: a longitudinal study from urban Vellore

Abstract: AbstractObjective:Early childhood factors can have persisting effects on development and cognition in children. We propose to explore the trends of Fe deficiency and Pb toxicity in early childhood and their association with child development at 2 years of age and cognition at 5 years.Design:Long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…Subsequent 6-month, 2-year and 3-year follow ups had 235 children, 228 children and 218 children respectively. Migration was the main cause for the loss to follow-up, as illustrated in other published articles from the same cohort [34].…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Subsequent 6-month, 2-year and 3-year follow ups had 235 children, 228 children and 218 children respectively. Migration was the main cause for the loss to follow-up, as illustrated in other published articles from the same cohort [34].…”
Section: Resultsmentioning
confidence: 61%
“…Iron de ciency in early childhood, when there is increased iron demand to optimize neuronal maturation, neurotransmitter synthesis, mitochondrial function and other iron dependent enzymes [44], can be detrimental as shown in the current analysis. This early childhood iron de ciency can have persisting effects on cognition in later life as evidenced by another analysis on the same cohort showing cumulative iron de ciency negatively impacting verbal, performance and processing speed domains of cognition at ve years of age [34]. That assessment had shown that more than 40% of children had iron de ciency at 15 and 24 months of age.…”
Section: Discussionmentioning
confidence: 94%
“…Subsequent 6-month, 2-year and 3-year follow ups had 235 children, 228 children and 218 children respectively. Migration was the main cause for the loss to follow-up, as illustrated in other published articles from the same cohort [38].…”
Section: Resultsmentioning
confidence: 61%
“…Iron de ciency in early childhood, when there is an increased iron demand to optimize neuronal maturation, neurotransmitter synthesis, mitochondrial function and other iron dependent enzymes [49], can be detrimental as shown in the current analysis. This early childhood iron de ciency can have persisting effects on cognition in later life as evidenced by another analysis on the same cohort showing cumulative iron de ciency negatively impacting verbal, performance and processing speed domains of cognition at ve years of age [38]. That assessment had shown that more than 40% of children had iron de ciency at 15 and 24 months of age.…”
Section: Discussionmentioning
confidence: 94%
“…Subsequent 6-month, 2-year and 3-year follow ups had 235 children, 228 children and 218 children respectively. Migration was the main cause for the loss to follow-up, as illustrated in other published articles from the same cohort [37].…”
Section: Resultsmentioning
confidence: 61%